Level of Likeness of Sausages Based on Type of Demersal Fish - Junianto, Junianto; Hafizha, Nazla Liyana; Falah, Rizki; Pamuji, Ginanjar (Torani Journal of Fisheries and Marine Science, 2025)
Processing fish meat as soon as possible is very important to increase its added value. The demand for processed fish products that is currently increasing is fish sausages. This research aims to determine the appropriate type of demersal fish meat as the main ingredient for making sausages based on the level of organoleptic preference. The research method used was experimental with a completely randomized trial design with three treatments. The three treatments are fish meat, pomfret, snapper and grouper meat.  The fish sausages obtained from the three treatments were observed for their level of preference for appearance, aroma, texture and taste.  The data obtained were analyzed using non-parametric statistics, the Friedman test and the multiple compression test. The Bayes method was used to determine the selected treatment. The results showed that the level of preference for the appearance, aroma, texture and taste of fish sausages was not influenced by the type of demersal fish meat used. Fish sausages made from snapper fish are preferred over sausages made from grouper or pomfret fish. The snapper sausage has a favorite level in the category of appearance, aroma, texture and taste. The average value of appearance favorability is 7.13 with a favorability percentage of 79.3%.   The average value of aroma preference level is 6.20 with a percentage preference level of 68.9%. The average value for texture preference level is 7.13 with a percentage preference level of 79.3%. The average value of taste preference level is 6.86 with a percentage preference level of 76.3%.